PERAN GURU DALAM PENGGUNAAN METODE CONCEPT SONG PADA KELAS 1B MADRASAH IBTIDAIYAH MIFTAHUSSOLIHIN TANJUNG REMA DARAT MARTAPURA - Ulfah, Emilya (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2025)
The use of learning methods can influence the learning process. Learning materials delivered using appropriate teaching methods are more effective than those delivered without any specific method. Therefore, an innovative approach is needed to make learning more active and enjoyable. One such method that can be used is the concept song method. The purpose of this research is to understand the teacher's role in using the concept song method in Class 1B at MI Miftahussholihin Tanjung Rema Darat Martapura, as well as to identify the supporting and inhibiting factors in implementing this method. This study employs a qualitative descriptive field research approach. The collected data is triangulated to ensure data authenticity and then analyzed qualitatively through data reduction, data presentation, and conclusion drawing. Based on the research findings, it can be concluded that the teacher's roles in using the concept song method in Class 1B at MI Miftahussholihin include: a. The teacher as a source of learning, b. The teacher as a facilitator, c. The teacher as a motivator; d. The teacher as a guide. The supporting factors in the implementation of the concept song method in Class 1B at MI Miftahussholihin are: a. Teachers, and b. Students. Meanwhile, the inhibiting factors in the implementation of the concept song method are: a. Facilities and infrastructure, b. Time constraints.